Returning (tales) - O'Brien, Edna (London PHOENIX Publisher, 1998)
A collection of short stories from the critically acclaimed author of "House of Splendid Isolation" and "Down by the River". The author evokes the sensations of childhood and adolescence in Ireland - the smells and tastes, the fears and joys, the sadness and confusions.
Keywords: Ireland -- Manners and customs